Bioresponsive functional nanogels as an emerging platform for cancer therapy. (3rd July 2018) - Huang, Dechun; Qian, Hongliang; Qiao, Haishi; Chen, Wei; Feijen, Jan; Zhong, Zhiyuan
ABSTRACT: Introduction : Bioresponsive nanogels with a crosslinked three-dimensional structure and an aqueous environment that undergo physical or chemical changes including swelling and dissociation in response to biological signals such as mild acidity, hyperthermia, enzymes, reducing agents, reactive oxygen species (ROS), and adenosine-5ʹ-triphosphate (ATP) present in tumor microenvironments or inside cancer cells have emerged as an appealing platform for targeted drug delivery and cancer therapy. Areas covered : This review highlights recent designs and development of bioresponsive nanogels for facile loading and triggered release of chemotherapeutics and biotherapeutics. The in vitro and in vivo antitumor performances of drug-loaded nanogels are discussed. Expert opinion : Bioresponsive nanogels with an excellent stability and safety profile as well as fast response to biological signals are unique systems that mediate efficient and site-specific delivery of anticancer drugs, in particular macromolecular drugs like proteins, siRNA and DNA, leading to significantly enhanced tumor therapy compared with the non-responsive counterparts. Future research has to be directed to the development of simple, tumor-targeted and bioresponsive multifunctional nanogels, which can be either constructed from natural polymers with intrinsic targeting ability or functionalized with targeting ligands. We anticipate that rationally designed nanotherapeutics based on bioresponsive nanogels will become available for future clinical cancer treatment. Abbreviations : AIE, aggregation-induced emission; ATP, adenosine-5ʹ-triphosphate; ATRP, atom transfer radical polymerization; BSA, bovine serum albumin; CBA, cystamine bisacrylamide; CC, Cytochrome C; CDDP, cisplatin; CT, computed tomography; DC, dendritic cell; DiI, 1, 1ʹ-dioctadecyl-3, 3, 3ʹ, 3ʹ-tetramethylindocarbocyanine perchlorate; DOX, doxorubicin; dPG, dendritic polyglycerol; DTT, dithiothreitol; EAMA, 2-(N, N-diethylamino)ethyl methacrylate; EPR, enhanced permeability and retention; GrB, granzyme B; GSH, glutathione tripeptide; HA, hyaluronic acid; HAase, hyaluronidases; HCPT, 10-Hydroxycamptothecin; HEP, heparin; HPMC, hydroxypropylmethylcellulose; LBL, layer-by-layer; MTX, methotrexate; NCA, N-carboxyanhydride; OVA, ovalbumin; PAH, poly(allyl amine hydrochloride); PBA, phenylboronic acid; PCL, polycaprolactone; PDEAEMA, poly(2-diethylaminoethyl methacrylate); PDGF, platelet derived growth factor; PDPA, poly(2-(diisopropylamino)ethyl methacrylate); PDS, pyridyldisulfide; PEG, poly(ethylene glycol); PEGMA, polyethyleneglycol methacrylate; PEI, polyethyleneimine; PHEA, poly(hydroxyethyl acrylate); PHEMA, poly(2-(hydroxyethyl) methacrylate; PNIPAM, poly( N -isopropylacrylamide); PMAA, poly(methacrylic acid); PPDSMA, poly(2-(pyridyldisulfide)ethyl methacrylate); PTX, paclitaxel; PVA, poly(vinyl alcohol); QD, quantum dot; RAFT, reversible addition-fragmentation chain transfer; RGD, Arg-Gly-Asp peptide; ROP, ring-opening polymerization; ROS, reactive oxygen species; TMZ, temozolomide; TRAIL, tumor necrosis factor-related apoptosis inducing ligand; VEGF, vascular endothelial growth factor.